Projeto político e as agências reguladoras no Brasil: o caso da Anatel nos governos Fernando Henrique Cardoso (1995- 2002) e Luiz Inácio Lula da Silva (2003-2010) - Santos, Fabiano Brito dos (2015)
In this study, the general objective, we seek to investigate whether there is, and how it is constructed different conceptions of 'regulation' within the framework of public policy and government management between the governments of Presidents Fernando Henrique Cardoso - FHC (1995-2002) and Luiz Inacio Lula da Silva - Lula (2003-2010). In order to do so, we conducted an investigation on the functioning of the National Telecommunications Agency (ANATEL) during the two governments. The quest to understand the development of the Brazilian telecommunications regulatory policy in the FHC government, and their (dis)continuity in the Lula government, are critical in the development of this research. In addition, it aimed to understand whether the regulation of telecommunications is promoted by the State in order to stimulate competition in the market and to identify how this process occurs. Thus, based on the analysis of the law and the the main policy agents within this sector in Brazil, we seek to understand how they act, what are their main interests, conflicts and projects, and finally, try to identify the elements that help to understand the relationship between Anatel (a decentralized state agency) and the Federal Government (as a transitional agent in the state).